The importance of english language learning in primary schools in the era of globalization - Saputri, Dhea Sylvia Ekha Tom (International Conference on Education in Primary and Early Childhood, Marine, Computer Information, and Logistics, 2025)
This research aims to gather information on the importance of English language learning in primary schools in the era of globalization. This research method uses literature studies, such as analysis and also review of books, articles, and other relevant sources to answer the importance of English language learning in primary schools in the era of globalization. The results of this study inform that the English language skills of Indonesians are still low in the eyes of the world, this shows that the important role of global language can advance our lives. In the era of globalization related to science, education, technology, health, business, politics, and in other fields are always written using English. Therefore, the role and challenges of English in the era of globalization will affect the development and progress of the Indonesian nation in the eyes of the world. But it is unfortunate that the English language skills of Indonesians are still very low, so it is important that English is taught since elementary school. There must be a habit of speaking English from an early age. Make English learning a compulsory subject at school.